RNA-Seq employing a novel rRNA depletion strategy reveals a rich repertoire of snoRNAs in Euglena gracilis including box C/D and Ψ-guide RNAs targeting the modification of rRNA extremities. Issue 10 (3rd October 2018) - Moore, Ashley N.; McWatters, David C.; Hudson, Andrew J.; Russell, Anthony G.
ABSTRACT: Previous mRNA transcriptome studies of Euglena gracilis have shown that this organism possesses a large and diverse complement of protein coding genes; however, the study of non-coding RNA classes has been limited. The natural extensive fragmentation of the E. gracilis large subunit ribosomal RNA presents additional barriers to the identification of non-coding RNAs as size-selected small RNA libraries will be dominated by rRNA sequences. In this study we have developed a strategy to significantly reduce rRNA amplification prior to RNA-Seq analysis thereby producing a ncRNA library allowing for the identification of many new E. gracilis small RNAs. Library analysis reveals 113 unique new small nucleolar (sno) RNAs and a large collection of snoRNA isoforms, as well as the first significant collection of nuclear tRNAs in this organism. A 3′ end AGAUGN consensus motif and conserved structural features can now be defined for E. gracilis pseudouridine guide RNAs. snoRNAs of both classes were identified that target modification of the 3′ extremities of rRNAs utilizing predicted base-pairing interactions with internally transcribed spacers (ITS), providing insight into the timing of steps in rRNA maturation. Cumulatively, this represents the most comprehensive analysis of small ncRNAs in Euglena gracilis to date.